Diplomasi Pertahanan Indonesia Dalam Pencapaian Keamanan Siber Melalui ADMM-Plus Tahun 2014-2019 - Samuel Mangara Sianturi (LITERATUS, 2021)
Cyber ??security issues began to emerge along with advances in the field of information technology and the rapid increase in internet use. However, the greater the need for the internet in the daily activities of the world community, the more potential international security threats arise from activities within the cyber scope. Given the "borderless" nature of cybercrime, it is necessary to deal with other countries. Indonesia's participation in ADMM-Plus illustrates Indonesia's efforts to achieve national interests, namely cyber security through the external environment. This study aims to discuss Indonesia's defense diplomacy in achieving cyber security through ADMM-Plus 2014-2019. By using defense diplomacy theory and qualitative methods, this research illustrates that Indonesia's diplomacy in ADMM-Plus is still at an early stage, so it is difficult to say that the diplomacy has not been maximized. However, the presence of ADMM-Plus has a positive impact on Indonesia, especially in terms of cyber security.